Lightning Monitoring Integrated System - Cruz, Michell; Lopes, Marcio; Vieira, Alen; Santos, Flávio; Shinkai, Ricardo; Nogueira, Daniele; Carvalho, Marissa; Nazaré, Anderson (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2019: Anais do X Workshop de Computação Aplicada a Gestão do Meio Ambiente e Recursos NaturaisDO - 10.5753/wcama.2019.6435, 2019)
Lightning is a natural phenomenon and presents severe risks to people and animals, as well as affects several segments of the productive sector. A web-based lightning monitoring system has been developed to integrate different lightning detection systems, as well as to generate spatial and tabular data and products, capable of assisting specialists and decision makers. The system also allows combining lightning data with satellite images, increasing the capacity of analysis in near real time. This tool proved to be stable and efficient, with an intuitive interface that facilitates interaction with users.